НАЦІОНАЛЬНА РЕГЛАМЕНТАЦІЯ МІЖРЕГІОНАЛЬНОГО СПІВРОБІТНИЦТВА - Rohozian, Yu.S. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2016)
The article identified and analyzed the components of the system regulatory framework of interregional cooperation based on the principles and priorities of the state policy in Ukraine. The main provisions in the area of interregional cooperation are considered to be implemented in legislation in accordance with the Agreement on Association between Ukraine and the EU. REFERENCES1. Bielien’kyj P. and Mikula N. (2011), Forming and development of the system of interregional and transfrontal collaboration is in Ukraine, Rehional’na ekonomika, vol. 3, pp. 61-73.2. The Verkhovna Rada of Ukraine (2004), The Law of Ukraine: About a transfrontal collaboration, available at:http://zakon0.rada.gov.ua/laws/show/1861-15 (Accessed 25 may 2016).3. The Verkhovna Rada of Ukraine (1995), The Law of Ukraine: About tacking of Ukraine to the charter of CE,available at: http://zakon4.rada.gov.ua/laws/show/398/95-вр (Accessed 25 may 2016).4. The Verkhovna Rada of Ukraine (1995), The Law of Ukraine: About tacking to the European charter of localself-government, available at: http://zakon2.rada.gov.ua/laws/show/994_036 (Accessed 25 may 2016).5. Lukash O.A. (2012), Forming of the methodical going is near the estimation of efficiency of frontier collaboration, Mekhanizm rehuliuvannia ekonomiky, vol. 1, pp. 145-154.6. Nazarenko O.M. (2004), Osnovy ekonometryky [Bases of econometrics], Tsentr navchal’noi literatury, Kyiv, Ukraine.